LEGAL PROTECTION AGAINST A NOTARY ALLEGED TO COMPLETE MALPRACTICE IN THE PROCESS OF MAKING OUTENTIC DEEDS - Sunardi, Sunardi; Rokhim, Abdul; Fabrila, Virly (Universitas Islam Malang, 2022)
A notary is a public official who is authorized by the state to make an authentic deed. On this basis, a legal protection is needed for a Notary if in carrying out his duties he is suspected of committing malpractice in the process of making an authentic deed as regulated in Article 38 of Law number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the position of a Notary, The formulation of the problem of Legal Protection Against Notary Positions Who Are Suspected of Malpractice in the Process of Making Authentic Deeds, Law Enforcement Procedures Against Notary Positions in Legal Protection Who Are Allegedly Conducting Malpractice in the Process of Forming Authentic Deeds through the Nortary Honorary Council according to the Law on Notary Positions the method used in This research is a normative research with a statutory approach. The results of the research on the legal protection of the position of a notary who is suspected of committing malpractice in the process of making an authentic deed. In making the deed, it must be in accordance with the regulations of Law No. 2 of 2014 article 38 so that the deed becomes an authentic deed that has perfect proof. The summons of investigators must be through the Notary Honorary Council (MKN) can be carried out repressively because it is related to the application of article 66 paragraph (1) UUJN-P, namely in giving approval or refusal of requests for investigators who want to summon a Notary in the Judicial Process. The existence of the Notary Honorary Council (MKN) basically replaces the role of the Regional Supervisory Council (MPD) as the Legal Protection Agency for Notaries. aims to avoid arbitrary actions from investigators who want to summon a Notary in the trial. Law Enforcement Procedures for the position of a Notary in his Legal Protection who are suspected of committing Malpractice in the process of forming an Authentic deed through the Honorary Council as regulated in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 25 of 2020 concerning Duties and Functions, Terms and Procedures for Appointment and Dismissal , Organizational Structure, Work Procedure and Budget of the Notary Honorary Council 1) Submit a written application for those who feel disadvantaged or investigators to MKN. 2) The Chairperson of the Regional Notary's Honorary Council is obliged to provide an answer in the form of approval or rejection of the application within 30 (thirty) working days from the date of receipt of the application. Then if within that period of time no response is received, the Regional MKN is considered to have received a request for approval (Article 27 paragraphs 4 and 5)Keywords. Notary, Malpractice, Legal Protection..